Precision Land Leveling technology will lead to potential benefits of large saving in irrigation water, energy with mitigation co-benefits - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The OICR on "Precision Land Leveling technology will lead to potential benefits of large saving in irrigation water, energy with mitigation co-benefits" was started in January. A research proposal is also developed - which CIMMYT was leading. CIMMYT started the preliminary survey for the questionnaire preparation in January and February, it couldn’t move any further due to Covid-19, lockdowns and travel restrictions.